Klong Niras of Prince Abhai: A Review of The Author Purpose of Writing and Study of The Path That Aappears in Niras - Klaisuwan, Natawut (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This academic article aims to achieve three objectives: 1. to review the author of the text, 2. to review the purpose of the composition, and 3. to study Niras poems and reorganize its sequence. The study finds that Prince Aphai, the son of King Taisa, is the author of the Niras poems. The purpose of the composition was to express the sorrow of separation and longing for his lover, and to describe the journey to venerate sacred objects at Khao Samokhon. Upon analyzing the text and reordering the verses, the study reveals that the journey described in the poem starts from Phra Nakhon Si Ayutthaya, proceeding north along the Lopburi River, passing through various locations, including Pho Sam Ton, Chao Pluk, Lopburi, Khao Samokhon, and then continuing to Phra Phutthabat Saraburi. The journey then heads south to Bang Khamod, Ban Pho Taeng, Bang Sai, Ko Phra, and Ko Rian, before returning to Phra Nakhon Si Ayutthaya. It is suggested that Prince Aphai may have undertaken this journey to explore the route in preparation for potential military action that could arise between him and King Boromakot, his uncle, who held the position of Chao Phaya Uparat (Crown Prince).